2015
DOI: 10.1159/000381138
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Calcification, Intraplaque Hemorrhage and Lipid Core within the Asymptomatic Atherosclerotic Carotid Plaque: The Rotterdam Study

Abstract: Background: There is a growing amount of evidence suggesting that the composition of carotid atherosclerotic plaques may be of clinical relevance. Yet, little is known on the coexistence of potentially vulnerable and stabilizing components within asymptomatic plaques. Therefore, in this study we set out to investigate the coexistence of intraplaque calcification, hemorrhage and lipid core within the carotid artery using a multi-modality imaging approach. Methods: In 329 subjects from the population-based Rotte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 28 publications
1
34
2
Order By: Relevance
“…However, as all examinations were performed by the same echocardiographers, we believe that this has not introduced any systematic error, especially because VTI ratio is a relative parameter and not strongly affected by angulation of the TEE probe. Moreover, TEE has only limited capabilities in evaluation of the internal structure of plaques, which is relevant for differentiating between stable and potentially vulnerable plaques [18,19]. In this context, MRI [20] and CT imaging [21] or dedicated ultrasound techniques [22,23] may provide additional information; however, those techniques are mostly designed for carotid plaque imaging and not suitable for the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…However, as all examinations were performed by the same echocardiographers, we believe that this has not introduced any systematic error, especially because VTI ratio is a relative parameter and not strongly affected by angulation of the TEE probe. Moreover, TEE has only limited capabilities in evaluation of the internal structure of plaques, which is relevant for differentiating between stable and potentially vulnerable plaques [18,19]. In this context, MRI [20] and CT imaging [21] or dedicated ultrasound techniques [22,23] may provide additional information; however, those techniques are mostly designed for carotid plaque imaging and not suitable for the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque hemorrhage has already been considered an important vulnerable plaque component that was shown to be associated with increased risk of stroke in clinical studies. [26][27][28] In addition, intraplaque hemorrhage noninvasively detected on magnetic resonance imaging was demonstrated to be a strong predictor for cerebrovascular events and might therefore be used for noninvasive risk stratification. [29][30][31] However, contradictory results have also been published showing that there is no association between plaque hemorrhage and microembolic signals 32 or the risk of stroke on a histopathologic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although Davaine et al 34 showed that vascular calcification is associated with plaque stability, other studies revealed ambiguous results. 26,33,35 Howard et al 33 did not find any relationships between calcification, intraplaque hemorrhage, or lymphocyte infiltration and stroke occurrence. In accordance with the latter findings, our study confirmed the assumption that increased calcification or higher amounts of inflammatory infiltration were also not associated with a history of neurological symptoms.…”
mentioning
confidence: 95%
“…16 An additional study of patients with symptomatic plaques (recent TIA, stroke, or amaurosis fugax) versus asymptomatic patients with critical stenosis found that the percentage of plaque calcification area was 2-fold greater in asymptomatic-versus-symptomatic plaques, and there was an inverse relationship between calcification and macrophage infiltration. 17 A different study investigating 611 carotid plaques by CT and MR imaging found that larger calcification volume was associated with higher IPH prevalence and a lower lipid core prevalence, suggesting that calcification may not be a stabilizing factor. 18 However, these studies evaluated total calcification volume or its binary presence or absence, and adventitial calcification coupled with soft plaque has not yet been addressed, to our knowledge.…”
mentioning
confidence: 99%